PROBLEM KETIDAKPATUHAN TERHADAP PUTUSAN MAHKAMAH KONSTITUSI TENTANG PENGUJIAN UNDANG-UNDANG - Widayati Widayati (Jurnal Pembaharuan Hukum, 2017)
Article 24C Paragraph (1) of the 1945 Constitution of the The Republic of Indonesia authorizes the Constitutional Court to hear at the first and final level the decission of wich of to examine the law againts the Constitution. In the elucidation of Article 10 Paragraph (1) of the law of Constitutional Court, the final decission shall obtain a permanent legal force from the time of speech and no legal remedy can be taken. The final verdict of the Constitutional Court examining the law is immediately applicable, and some require the follow up of the legislators by forming new laws, or amending existing laws. Often, the legislators do not obey the Cosntitutional Court’s decission. Non-compliance can occur because there are not sanctions againts non-compliance, and also the Constitutional Court does not haven an instrumental or execution in charge of ensuring the execution of its verdict. Therefore, efforts are needed to ensure that the Co nstitutional Courtas a judicial institution remains authoritative and is not abandoned by justice seekers.